Understanding Cellular Respiration through Simulation Using Lego® as a Concrete Dynamic Model - Michiel Dam; Koen Ottenhof; Carla Van Boxtel; Fred Janssen (MDPI AG, 2019)
Out of all the complex systems in science education curricula, cellular respiration is considered to be one of the most complex and abstract processes. Students are known to have low interest and difficulties in conceptual understanding of cellular respiration which provides a challenge for teaching and learning. In this study, we took literature about modelling and teaching and learning cellular respiration as a starting point for the design of a concrete dynamic model in which students (n = 126) use Lego® to simulate the process of cellular respiration. Students used the simulation embedded in the context of finding the efficiency of a sediment battery as a future source of green energy and we tested the effects on conceptual learning and situational interest in an experimental study. Results on conceptual learning show that both experimental and control groups had comparable results in the test. The questions that students in the experimental group asked during enactment, however, gave notice of a focus on both isolated component parts as well as modes of organization at higher organizational levels which is linked to how biologists mechanistically understand complex systems. Both groups report a similar high measure to which the topic is meaningful in real life (situational interest value), whereas the enjoyment (situational interest feeling) was significantly increased in the experimental group. Furthermore, students report specific advantages (e.g., I now understand that one acid chemically changes into another and they do not just transfer atoms) and disadvantages (e.g., time issues).